1989
DOI: 10.1007/bf01871734
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sodium and pyruvate interactions of the two carrier systems specific of mono- and di- or tricarboxylic acids by renal brush-border membrane vesicles

Abstract: The experiments reported in this paper aim at characterizing the carboxylic acid transport, the interactions of pyruvate and citrate with their transport sites and specificity. The study of these carriers was performed using isotopic solutes for the influx measurements in brush-border membrane vesicles under zero trans conditions where the membrane potential was abolished with KCl preloading with valinomycin or equilibrium exchange conditions and delta psi = 0. Under zero trans condition and delta psi = 0, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…L-lactate ϭ 235 Ϯ 24 M and nicotinate ϭ 296 Ϯ 88 M (13,14,22,23). Taken together these data demonstrate that affinity of zSMCTn for L-lactate and nicotinate are ϳ10 times 7 and ϳ30 times lower than the affinity of zSMCTe for the same compounds, respectively (compare Fig. 4 with Fig.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…L-lactate ϭ 235 Ϯ 24 M and nicotinate ϭ 296 Ϯ 88 M (13,14,22,23). Taken together these data demonstrate that affinity of zSMCTn for L-lactate and nicotinate are ϳ10 times 7 and ϳ30 times lower than the affinity of zSMCTe for the same compounds, respectively (compare Fig. 4 with Fig.…”
Section: Resultssupporting
confidence: 61%
“…Several studies have also reported the kinetics of renal Na ϩ /MC cotransport (7,8,12,34,40). These studies suggested the presence of two kinetically different Na ϩ /MC cotransport systems with one having higher affinity for MCs than the other.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The authors reported two sodium-driven electrogenic processes from whole cortex, pars convoluta, and pars recta, one of high affinity and the other of low affinity. Other reports in the literature have also confirmed the presence of a sodium-dependent transport process for L-lactate or pyruvate in mammalian kidney (BaracNieto et al, 1980;Nord et al, 1982;Mengual et al, 1989). Recently, the high-affinity sodium-dependent transport system for monocarboxylates has been identified as SLC5A8, a facilitated glucose transporter family member (Li et al, 2003;Miyauchi et al, 2004), and the low-affinity sodium-dependent transporter for monocarboxylates as SLC5A12 (Srinivas et al, 2005).…”
Section: Downloaded Frommentioning
confidence: 84%
“…In the kidney, SMCT1 is expressed in the apical membrane of tubular epithelial cells and is mainly limited to the S3 section of the proximal tubule. It was hypothesized that SMCT1 is involved in renal reabsorption of lactate and pyruvate (Gopal et al, 2007b;Ganapathy et al, 2008), because sodium-dependent transport of these monocarboxylates has been observed in the kidney (Barac-Nieto et al, 1980;Mengual et al, 1989). Moreover, SLC5A8-deficient or knockout mice exhibited increased urinary excretion of lactate (Frank et al, 2008).…”
mentioning
confidence: 99%